2017
DOI: 10.1111/jam.13609
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vaccination as aSalmonellaTyphimurium reduction strategy on pig farms

Abstract: Aims: The control of Salmonella in pig production is necessary for public and animal health, and vaccination was evaluated as a strategy to decrease pig prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Farms were geographically diverse, and loosely representative of the finisher-only pig industry in GB; no farms were selected from the North West, Wales or Scotland (Supplementary Table S1) (Pig Health and Welfare Council, 2017). The farms selected were not random but an opportunistic selection of 53 farms participating in a Salmonella study, and these included 19 farms with low prevalence of Salmonella (Martelli et al, 2017;Smith et al, 2017Smith et al, , 2018. Three additional farms were recruited solely for this study.…”
Section: Farm Recruitment and Samplingmentioning
confidence: 99%
“…Farms were geographically diverse, and loosely representative of the finisher-only pig industry in GB; no farms were selected from the North West, Wales or Scotland (Supplementary Table S1) (Pig Health and Welfare Council, 2017). The farms selected were not random but an opportunistic selection of 53 farms participating in a Salmonella study, and these included 19 farms with low prevalence of Salmonella (Martelli et al, 2017;Smith et al, 2017Smith et al, , 2018. Three additional farms were recruited solely for this study.…”
Section: Farm Recruitment and Samplingmentioning
confidence: 99%
“…Increasing the quality of colostrum (i.e. the amount of immunoglobulins) through vaccination of pregnant sows before farrowing should be considered another potential strategy to protect suckling piglets from infection [43, 4547] and even Salmonella shedding in older pigs [48, 49].…”
Section: Discussionmentioning
confidence: 99%
“…Maternally derived immunity does not interfere with the effect of the vaccination of piglets, on the contrary, Rösler et al showed that vaccinated piglets from vaccinated sows had significantly lower infection levels after challenge than vaccinated piglets from unvaccinated sows [25]. The effectiveness of Salmoporc® is well documented [26][27][28][29] for the reduction of colonisation and shedding of Salmonella Typhimurium, sometimes even in the unvaccinated progeny of vaccinated sows [30,31]. However, to our knowledge, no studies exist that followed a vaccinated herd to the point where Salmonella Typhimurium could no longer be isolated from faecal and dust samples.…”
Section: Introductionmentioning
confidence: 99%